Anatomical Variations in Muscles Taking Attachment at Medial Carpal Region - Nazia Quadir; Ashwini Kudopa; Sandeep Marskole; Ranjana Agrawal; Rajveer S. Chourasia (Journal of Pharmacy and Bioallied Sciences)
Background: The hypothenar muscles (Abductor Digiti Minimi (ADM), Flexor Digiti Minimi (FDM), Opponens Digiti Minimi (ODM)) and Flexor Carpi Ulnaris (FCU) exhibit anatomical variations that may contribute to ulnar nerve compression in Guyon’s canal and impact neurovascular pathways. Materials and Methods: Fifty cadaveric upper limbs were analyzed for variations in origin, insertion, nerve supply, and accessory structures of the hypothenar muscles and FCU, with a statistical assessment of their prevalence. Results: ADM had a single belly in 80% and two bellies in 20%, with 10% showing additional muscle slips and 30% exhibiting nerve supply variations. FDM originated from the hook of hamate in 74%, while 26% had a fibromuscular arch, 22% of which enclosed the deep ulnar nerve and artery. ODM was present in 98%, with the ulnar nerve and artery piercing it in 32%. FCU had a normal insertion in 98%, while 2% exhibited an additional tendinous slip. Conclusion: These variations are clinically significant in ulnar nerve entrapment and vascular compression syndromes. Recognizing them is essential for accurate diagnosis and optimized surgical interventions.